Knowledge and the Norm of Assertion An Essay in Philosophical Science - Turri, John (Open Book Publishers, 2016)
"Language is a human universal reflecting our deeply social nature. Among its essential functions, language enables us to quickly and efficiently share information. We tell each other that many things are true-that is, we routinely make assertions. Information shared this way plays a critical role in the decisions and plans we make. In Knowledge and the Norm of Assertion, a distinguished philosopher and cognitive scientist investigates the rules or norms that structure our social practice of assertion. Combining evidence from philosophy, psychology, and biology, John Turri shows that knowledge is the central norm of assertion and explains why knowledge plays this role. Concise, comprehensive, non-technical, and thoroughly accessible, this volume quickly brings readers to the cutting edge of a major research program at the intersection of philosophy and science. It presupposes no philosophical or scientific training. It will be of interest to philosophers and scientists, is suitable for use in graduate and undergraduate courses, and will appeal to general readers interested in human nature, social cognition, and communication."